Some properties of geodesic semi E-b-vex functions - Kilicman, Adem; Saleh, Wedad (De Gruyter Open, 2015)
In this study, we introduce a new class of function called geodesic semi E-b-vex functions and generalized geodesic semi E-b-vex functions and discuss some of their properties.